(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
Data preprocessing is an crucial phase within the records evaluation pipeline, pivotal in ensuring that uncooked statistics may be efficiently utilized to extract meaningful insights. This evaluates paper offers a complete manual to the intricate process of statistics preprocessing, providing a step-by using-step assessment of essential strategies and best practices for refining uncooked records into smooth and usable datasets. The paper encompasses diverse facts preprocessing obligations, including records cleaning, lacking price imputation, function engineering, and outlier detection, underscoring their important position in improving statistics great. Drawing from the modern studies and sensible tips, this review equips facts analysts and scientists with the expertise and gear needed to bolster information reliability and relevance in a mess of programs.